A variant of the long song training curriculum - Myagmarsuren, Dorjdagva (Mongolian Journal of Arts and Culture, 2024)
The article is written based on many years of study, research and experience regarding the preservation, protection, and inheritance of long songs, as well as its continuity and vision in the future. The questions of “What are the most potential methods to preserve centuries-old historical memory, conscientious, and physical experiences preserved in the idealogy and meanings of the long-songs by passing down long songs? What will be the approaches and tendencies of Mongolian vocal art of Urtyn-Duu (Long-song) in the 21st century? What will be the distinct features and characteristics to distinguish from the historical figures of the past centuries? What will be lost and what will be inherited?” were taken into consideration. A pilot study was conducted to develop and implement an independent training curriculum as the main platform and field of searching for the answer to the questions. As a result, the study led to a issue that “An independent curriculum, its implementation, and results will determine the long-song of the 21st century”. Уртын дууны сургалтын хөтөлбөрийн нэгэн хувилбар Хураангуй: Уртын дууны хадгалалт, хамгаалалт, өвлөн уламжлах үйл явц болон түүний оршиж ирсэн, цаашид хэрхэн оршин байх тухайд гүйцэтгэсэн олон жилийн судалгаа, мэдлэг-туршлагадаа үндэслэн тус өгүүллийг бичив. “Уртын дууг өвлөн уламжлах замаар үзэл санаа, утга агуулгад нь хадгалагдсан олон зуун жилийн түүхэн ой санамж, ухамсрын болон бие мах бодийн туршлагаас ямар арга замаар авч үлдэх вэ?, монгол уртын дууны урлаг XXI зууны эхэнд ямар чиглэлтэй болох вэ?, өнгөрсөн олон зууны түүхэн дүрүүдээсээ юугаар ялгарах вэ?, юуг нь гээж, юуг нь өвлөх вэ? гэсэн асуултууд дэвшүүлэн ажиллав. Асуултынхаа хариултыг хайх үндсэн талбараар нь бие даасан сургалтын хөтөлбөр зохион хэрэгжүүлэх туршилт судалгаа гүйцэтгэв. Ингэснээр “Бие даасан сургалтын хөтөлбөр, түүний хэрэгжилт, үр дүн нь XXI зууны уртын дууг тодорхойлно” гэсэн гаргалгаанд хүрэв. Түлхүүр үгс: уламжлал, орчин үе, мэдлэг, ур чадвар, хандлага